Ujjayini : kāvyakhyāyika - Kurup, O. N. V., 1931- (Ḍi. Si. Buka : Distributors, Current Books, 1994)
Extended verse work about poet Kālidāsa, and Ujjain where he flourished; includes a group discussion of the work with the poet by fellow-writers.